Human herpesvirus‐6 viremia is not associated with poor clinical outcomes in children following allogeneic hematopoietic cell transplantation. (29th August 2015) - Violago, Leah; Jin, Zhezhen; Bhatia, Monica; Rustia, Evelyn; Kung, Andrew L.; Foca, Marc D.; George, Diane; Garvin, James H.; Sosna, Jean; Robinson, Chalitha; Karamehmet, Esra; Satwani, Prakash
Abstract HHV‐6 is an evolving pathogen in the field of AlloHCT. However, the impact of HHV‐6 on AlloHCT outcomes remains to be elucidated. We studied the incidence and clinical impact of HHV‐6 viremia in children following AlloHCT. One hundred consecutive children were monitored weekly by plasma PCR for the first 180 days following AlloHCT for HHV‐6, CMV, EBV, and ADV. HHV‐6 viremia was defined as plasma PCR >1000 viral copies/mL. The median age was nine yr. Following AlloHCT, 19% (95% CI 11.3–26.7%) of patients had HHV‐6 viremia, with the highest incidence of reactivation (14/19, 73%) occurring during day +15‐day +98. The proportion of platelet engraftment by day +180 was lower in patients with HHV‐6 viremia (58%) than in those without HHV‐6 viremia (82%), p = 0.028. Delay in neutrophil and platelet engraftment was not associated with HHV‐6 viremia in multivariate analysis. Similarly, HHV‐6 viremia was not associated with TRM in multivariate analysis (p = 0.15). In summary, HHV‐6 viremia is prevalent in pediatric AlloHCT recipients. Based on our study results, we recommend that HHV‐6 PCR should only be performed on clinical suspicion.